On the Rooster and the Pearl: exploring Lithuanian literary consciousness in the 19th century - Tamošiūnienė, Aušra (Respectus Philologicus, 2024)
This article examines seven different renditions of Aesop’s fable “The Rooster and the Pearl”, written by various 19th-century Lithuanian authors. The aim is to show how these texts reflect the demands of early readers and the literary consciousness of 19th-century Lithuanian society. The differences in the texts and their significant features are revealed by comparing them with each other and with the original sources, where such sources can be identified. Of particular interest is the inclusion of Lithuanian elements in these narratives, typically used for their evocative imagery or to capture the reader’s attention. The influence of social and cultural life on literature is bidirectional. As societies change over time in cultural, ethical and other ways, these changes inevitably affect literary production. The ethical perspective is relevant to the plot of The Rooster and the Pearl, but the specificity of the texts analysed is determined more by aesthetic and persuasive qualities, thus serving as precursors to shifts in literary consciousness.
Keywords: fable; XIX century; literary consciousness; author and reader